INTENSITY OF REPURCHASE OF MADAM GIE COSMETIC PRODUCTS BASED ON CONSUMER PERSPECTIVE (ESPECIALLY BEAUTY VLOGGER IN BANDUNG CITY) - S, Shafiza Adira; N, Saskia Permata Putri R.; Argawinata, RM; Apriyani, Vinny; Elizah, Salma Nasya; Hapsari, Ayuningtyas Y. (CENTRAL ASIA AND THE CAUCASUS, 2022)
Cosmetics is one of the most important needs for womens in Indonesia, especially in the city of Bandung. With the development of time, the use of cosmetic products tends to increase. One of the most popular cosmetic brands for Indonesian women is Madam Gie Cosmetics. This study aims to determine what factors influence consumers' decisions to buy Madam Gie's cosmetic products. Determining the number of samples in this study using the Accidental Quota Sampling method so that 75 respondents were obtained, mostly consisting of teenagers/students while the rest were entrepreneurs and influencers. For processing and analyzing data in this study, using SPSS 20 as software to process data. The data obtained is by using a random sampling technique, then an analysis of the data obtained with qualitative data is carried out. Quantitative analysis includes: Multiple regression analysis, hypothesis testing through t test, and simultaneous hypothesis testing. Based on the results of the study it can be concluded that the price variable has a positive influence, means Price has no significant effect on the repurchase intention of Madam Gie's cosmetic products. On the other hand, product quality has an influence on repurchase intention. Affect positively and influential means product quality has a significant effect on repurchase intention.